Epidemiological study of cardiovascular risk factors among public transport drivers in rural area of Chittoor district of Andhra Pradesh - Udayar, Sharvanan Eshwaran; Sampath, Shankar; D., Arun; Sravan, Sai (International Journal Of Community Medicine And Public Health, 2017)
Background: Non communicable diseases (NCDs) are considered as one of the major health and development challenges of the 21st century, recent studies had demonstrated that transport drivers are at greater risk of developing cardiovascular diseases due to an incorrect diet, sedentary behavior, unhealthy lifestyles and obesity. The objective of the study was the study was conducted with the aim of assessing some cardiovascular risk factors and its relation to sociodemographic variables. Methods: Cross sectional study was carried out from Jan 2013 to June 2013 with transport drivers of APSRTC of Venkatagiri Kota. Data was collected regarding socio-demographic profile, diabetes, use of medication, tobacco and alcohol consumption, work schedules and perceived occupational problems and their blood pressure and anthropometry were also measured & analyzed using SPSS software. Results: 204 transport drivers were studied. Out of95 tobacco consumers 68 were smokers and 27 were tobacco chewers and 110 subjects were alcohol consumers. Perceived reasons for smoking were it suppresses cold (27.94%) and enables to concentrate on work (20.58%). Perceived reasons for alcohol consumption were peer pressure (17.2%) and it suppresses cold (20%). Among 204 subjects 36.2% were pre-obese and 34.8% were obese with 23.05% of pre-hypertensive and 14.21% hypertensive. Duration of alcohol intake and tobacco use, BMI, WHR & WC were significantly associated with hypertension. Conclusions: There is a high prevalence of risk factors of cardiovascular disease with various perceived reasons and they were statistically significantly associated with hypertension.